Induksi dan Multiplikasi Tunas Jarak Pagar (Jatropha curcas L.) Secara In Vitro - , Lizawati; Trias Novita; Ragapadmi Purnamaningsih (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2009)
The conventional propagation of physic nut (Jatropha curcas) is difficult, because it requires a high number of mother plant, which is very limited. In vitro culture is an alternative technique to conventional one to solve the problem.  An experiment was done to obtain the best in vitro culture media for shoot induction and multiplication. This research was separated into two steps, (1) in vitro induction of explant growth, and (2) in vitro shoot multiplication.  Results showed that medium of WPM + 2.0 ppm BAP induced shoot and leaf better than the control.  The highest number of leaf axillary's multiplication was obtained from the medium WPM + 2.0 ppm BAP + 0.1 ppm NAA. Various medium formulations for the induction and multiplication of shoots resulted in highly leaf fall.  The use of DKW + 2.0 ppm BAP + 0.4 ppm TDZ + 3.0 ppm AgNO3 medium has effectively induced shoot multiplication and reduction of dehydrated leaf. Meanwhile, the used of DKW medium supplemented with 5 ppm kinetin resulted in the best shoot elongation.   Key words :  Induction, in vitro, Jatropha curcas, shoot, multiplication